Phosphorylated neurofilament heavy chain (pNfH) concentration in cerebrospinal fluid predicts overall disease aggressiveness (D50) in amyotrophic lateral sclerosis - Meyer, Julia; Gaur, Nayana; von der Gablentz, Janina; Friedrich, Bernd; Roediger, Annekathrin; Grosskreutz, Julian; Steinbach, Robert (Frontiers in Neuroscience, 2025)
IntroductionAmyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disorder, characterized by tremendous clinical heterogeneity that necessitates reliable biomarkers for the trajectory of the disease. The potential of phosphorylated Neurofilament-Heavy-chain (pNfH) measured in cerebrospinal fluid (CSF) to mirror disease progressiveness has repeatedly been suggested but is not applicable as outcome on an individual patient-level. This potential was probably obfuscated before due to imprecise clinical measures of disease progression that assumed a linear decline of motoric function over time. The primary objective was therefore to study if disease aggressiveness, as quantified via the D50 model, would reveal more stable correlations with pNfH.MethodsELISA-quantified pNfH CSF levels of 108 patients with ALS were comparatively analyzed in relation to three different measures of disease progression speed via analyses of covariance, linear and non-linear regressions, respectively. These were (a) the D50, depicting a patient’s overall disease aggressiveness, (b) cFL, the calculated functional loss-rate as locally derived parameter of progression speed, and (c) DPR, the disease progression-rate as more commonly used linear approximation of points lost per month in the ALS functional rating scale since symptom onset.ResultsAll analyses of covariance showed a significant main impact of the respective disease progression-speed parameter on pNfH, independent of disease phase, presence of frontotemporal dementia, analyzing laboratory, sex or clinical onset type, while only age revealed borderline additional influence. Notably, CSF pNfH concentration was independent of how far the disease had progressed, as neither disease phase nor a direct regression with the quantified disease accumulation at the time of lumbar puncture revealed a significant correlation. However, the parameter D50 quantifying aggressiveness showed the most significant impact on pNfH-levels, as compared to the cFL and even more evident in contrast to the DPR. This superiority of D50 was confirmed in direct linear and most evident in non-linear regressions with pNfH.ConclusionOverall disease aggressiveness in ALS, as quantified by D50, most robustly correlated with CSF pNfH-levels, independent of the time of collection during symptomatic disease. This opens perspectives to use CSF pNfH as a prognostic outcome measure for future therapeutic interventions in the sense of precision medicine.